Photoconductivity and photoluminescence features of γ-irradiated GaS₀.₇₅Se₀.₂₅‹Er› single crystals - Taghiyev, T.B. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2011)
The effect of γ-radiation with Е = 1.3 MeV energy and Dγ = 10…200 krad
dose on photoconductivity and photoluminescence features of GaS₀.₇₅Se₀.₂₅‹Er› single
crystals was studied. When analyzing the experimental data it was established that after
doping with the rare-earth element erbium N = 10¹⁸ cm⁻³ and γ-radiation the
photoconductivity value and the intensity of photoluminescence radiation increased in
the investigated samples. A defect-formation model explaining the observed
characteristics was proposed.